2016
DOI: 10.1038/srep19473
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome sequencing and gene expression profiling of spinach (Spinacia oleracea L.) leaves under heat stress

Abstract: Spinach (Spinacia oleracea) has cold tolerant but heat sensitive characteristics. The spinach variety ‘Island,’ is suitable for summer periods. There is lack molecular information available for spinach in response to heat stress. In this study, high throughput de novo transcriptome sequencing and gene expression analyses were carried out at different spinach variety ‘Island’ leaves (grown at 24 °C (control), exposed to 35 °C for 30 min (S1), and 5 h (S2)). A total of 133,200,898 clean reads were assembled into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
72
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 61 publications
(78 reference statements)
9
72
1
Order By: Relevance
“…Duan et al found that salicylic acid (SA), ethylene (ET) and abscisic acid (ABA) treatments had no influence on chloroplastic HSP70 expression in wheat [18]. Spinach HSP70 have sensitive response to heat [26][27][28]32], cold [28,47], water [26], wound [26] and heavy metal stress [9,12]. As showed in Figure 1 and Figure 2, the present study quantitatively analyzed the expression of spinach HSP70-9 at the transcriptional level in response to the EHs, BPA and PAEs in both single and combined pollution treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Duan et al found that salicylic acid (SA), ethylene (ET) and abscisic acid (ABA) treatments had no influence on chloroplastic HSP70 expression in wheat [18]. Spinach HSP70 have sensitive response to heat [26][27][28]32], cold [28,47], water [26], wound [26] and heavy metal stress [9,12]. As showed in Figure 1 and Figure 2, the present study quantitatively analyzed the expression of spinach HSP70-9 at the transcriptional level in response to the EHs, BPA and PAEs in both single and combined pollution treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Among these families, HSP70 family is the highly conserved and the most researched gene family [11,15,17,[20][21][22][23][24]. Studies have demonstrated that heat stress [15,[18][19][20][24][25][26][27][28][29][30][31][32], Cold stress [15,24,26,29,30], water stress [22,25,26,33,34], oxidative stresses [19,20,22], heavy metals [9,12,13,35], salt stress [13,19,20,22,34], light stress [27], and chemical contaminants [11,15,18,19,25,[35]…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome analysis of several plant species in response to temperature has revealed the involvement of heat stress responsive genes in the acquisition of thermo-tolerance (Li et al, 2013;Liao et al, 2015;Mangrauthia et al, 2016;Yan et al, 2016). For example, Liao et al (2015) identify potential candidate genes involved in high night-temperature response in thermo-tolerant and -sensitive rice lines.…”
Section: Introductionmentioning
confidence: 99%
“…Spinach leaf de novo transcriptome analysis under heat stress showed that up to 1130 genes were up-regulated as compared to the control. Among the identified heat-responsive genes, transcription factors play an important role in response to early heat stress (Yan et al, 2016). Additionally, genes involved in salt stress, organic acid metabolic and carotenoid metabolic represented a special mechanism in spinach response to heat stress (Yan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Dohm et al [10] sequenced spinach genome with the Beta vulgaris species and they identified a significant number of genes affecting agronomically important traits. Yan et al [11] showed the transcriptome and gene expression profile of spinach under the heat stress to elucidate its cold tolerance; they identified candidate genes so gene-gene interaction pathways might be found to understand the heat resistance mechanism in spinach in the future.…”
Section: Introductionmentioning
confidence: 99%